Efektivitas Metode Drill dan Kegiatan Muhadatsah Muhadhoroh untuk Meningkatkan Kecakapan Berbahasa Arab - Aulia Sifa Putri Anggraini (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2023)
The aim of this research is so that every student has the opportunity to master Arabic vocabulary (mufrodat) with correct pronunciation and meaning. This discussion discusses the effectivieness of using practice methods or getting used to course activities that use the drill, muhadatsah (conversation or dialogue which means exchanging thought or opinions regarding a certain topic), and muhadharah (deleviry of material or speech) in an effort to improve the Arabic vocabulary mastery of Mambaus Sholihin 2 Blitar students. Language is very important for humans, namely as a means of communication. Arabic is very important for humans, namely as a communication tool. Especially for students who study at Islamic Boarding School. The implementation of this activity is an effort by the management to realize the vision and mission of the institution, manely to become a modern Islamic Boarding School or called a modern Islamic Boarding School which requires student to use Arabic ang English in their daily activities.